Les bénéfices sociaux et environnementaux des systèmes agricoles : une analyse ostromienne de trois terrains d’étude en France - Marielle Berriet-Solliec; Christophe Déprés; Colas Chervier; François-Gaël Lataste; Denis Lépicier; Hai Vu Pham; Virginie Piguet (Développement Durable et Territoires)
This article uses the Ostrom’s notion of socio-ecological system in order to characterize agricultural practices generating social and environmental benefits and to identify factors that ease or limit their implementation. The methodology is based on three case studies in France on sustainable agricultural practices in Langres, about preservation of water quality and quantity in Volvic and on agro-pastoralism in the Cévennes National Park. Five main factors could be identified that point to the importance of public intervention when it matches with concerted local governance between public and private actors at different management scales.